Emerging Role of Dermal White Adipose Tissue in Modulating Hair Follicle Development During Aging - Chen, Jian; Fan, Zhe-Xiang; Zhu, De-Cong; Guo, Yi-Long; Ye, Ke; Dai, Damao; Guo, Zhi; Hu, Zhi-Qi; Miao, Yong; Qu, Qian (Frontiers in Cell and Developmental Biology, 2021)
Hair follicle stem cells extensively reprogrammed in the aging process, manifesting as diminished self-renewal and delayed responsiveness to activating cues, orchestrated by both intrinsic microenvironmental and extrinsic macroenvironmental regulators. Dermal white adipose tissue (dWAT) is one of the peripheral tissues directly adjacent to hair follicles (HFs) and acts as critical macroenvironmental niche of HF. dWAT directly contribute to HF aging by paracrine signals secretion. However, the altered interrelationship between dWAT and HF with aging has not been thoroughly understood. Here, through microdissection, we separated dWAT from skin of aged mice (18 months) and young mice (2 months) in telogen and depilation-induced anagen for transcriptome comparing. Noteworthy, comparing with young dWAT, aberrant inflammatory regulators were recapitulated in aging dWAT of telogen, including substantial overexpressed inflammatory cytokines, matrix metalloproteinases, prostaglandin members. Nonetheless, with anagen initiation, inflammation programs were mostly abolished in aging dWAT and instead of which, impaired collagen biosynthesis, angiogenesis and melanin synthesis were identified. Furthermore, we confirmed the inhibitory effect on hair growth of CXCL1, one of the most significantly uprrgulated infammtion cytokines in aging dWAT. Besides, we also identified the under-expressed genes related to Wnt signaling fibroblast growth factor family members, and increased BMP signaling in aging dWAT, further unraveling the emerging role of dWAT in aging HFs malfunction. Finally, we proved that relieving inflammation of aging dWAT by injecting high-level veratric acid stimulated HF regenerative behavior in aged mice. Concomitantly, significantly decreased TNF-a, CCL2, IL-5, CSF2 and increased IL10 in dWAT was identified. Overall, the results elaborated on the complex physiological cycling changes of dWAT during aging, providing basis for potential regulatory effect of dWAT on aging HFs.